The Effect of Arm Muscle Explosion, Hands Eye Coordination and Achievement Motivation on Spin Pass Skills at DKI Jakarta Rugby Athletes - Agus Maulana Setiawan; Hidayat Humaid; Iwan Setiawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
This study aims to determine the effect of Arm Muscle Explosive Power, Hand Eye Coordination and Achievement Motivation on Spin Pass Skills in DKI Jakarta Rugby Athletes. The research sample was 45 DKI Jakarta Rugby Athletes. The research approach used in this study was multivariate associative, with survey methods and test and non-test techniques. The analysis technique uses a path analysis approach at a significance level of 0.05. the conclusion of each research finding shows (1) There is a direct influence between each independent variable Arm Muscle Explosive Power (X1), Hand Eye Coordination (X2), and Achievement Motivation (X3), (2) There is a direct effect of each independent variable Arm Muscle Explosive Power (X1), Hand Eye Coordination (X2), and Achievement Motivation (X3) have a direct influence on Spin Pass Skills (Y), (3) There is an indirect effect of Arm Muscle Explosive Power (X1) through Achievement Motivation (X3) on Spin Pass Skills. (Y). There is an indirect effect of Eye-Hand Coordination (X2) through Achievement Motivation (X3) on Spin Pass Skills. (Y). Thus, Spin Pass Skills can be improved through increased Arm Muscle Explosive Power, Hand Eye Coordination and Achievement Motivation",